EFFICIENCY OF URINE PUMPING IN THE HUMAN URETER - Ahmadu Bappah, Muhammad (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2016)
The efficiency of peristaltic pumping mechanism in the flow of urine from the kidneys to the bladder through the ureter is studied based on Liron‟s model, but with no applied external pressure gradient, in strict compliance with natural peristalsis situation as appears in physical organs. By applying the zeroth-order solutions, it is observed that in this study, the major contributing factor is the wave-plows (r) of the peristaltic motion of the flow tract rather than the Reynolds‟s number that has a direct bearing on the fluid property. But as would be expected, the Reynolds number appears in the generated axial pressure-gradient as well as the mean rate of mechanical work. The graph of variation of E with respect to r shows similar pattern as velocity profiles as shown in previous studies. This confirms the earlier assertion about the effect of the peristaltic motion.